Analysis of The Emergency Reasons in The Application of Marriage Dispensation at The Tenggarong Religious Court - Andar Yuni, Lilik (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2021)
The increase of the minimum marriage age is intended to reduce the number of child marriages. However, Article 7 section (2) of the marriage law revision states that marriage dispensation can be requested for emergency reasons if a deviation takes place. Consequently, marriage dispensations in various regions have drastically increased after the revision. Hence, judges’ active role is needed to adjudicate this case, including classifying the criteria of emergency reasons and judges’ considerations to grant the application of marriage dispensation. This study was normative and empirical legal research, and collected data through documentation and library study. The data source was secondary data in the form of primary legal materials, including Law no. 1 of 1974 concerning marriage, Law no. 16 of 2019 concerning amendments to Law Number 1 of 1974, the Supreme Court Regulation Number 5 of 2019 concerning Guidelines for Adjudicating Marriage Dispensation Cases and Granting Marriage Dispensation, and secondary legal materials including scientific journals and articles. The study approach was a study case, and the data were analyzed by descriptive analysis. This study found that “emergency reasons” as judges’ consideration in deciding a marriage dispensation at the Tenggarong Religious Court as were: (1) having been in a long period of relationship; (2) an unexpected pregnancy, (3) often going to a date, and (4) living in the same house as the prospective husband.